PENGARUH DEBIT AIR TERHADAP? PUTARAN?TURBIN?DAN?DAYA?OUTPUT? YANG?DIHASILKAN?PROTOTYPE PLTMH?DENGAN?TURBIN?KAPLAN - Ariestya Pamungkas, Ravinda; Arta Wijaya, I Wayan; Janardana, I Gusti Ngurah (Jurnal SPEKTRUM; Vol 8 No 2 (2021): Jurnal SPEKTRUM, 2021)
Kaplan turbine is suitable turbine to use in the place that have small water fall (head) but need big water discharge. The problem from this turbine is the turbine need high water discharge to test the related parameters but it is too difficult to do because the water discharge is not constant in the river. Based on the problems described, it is necessary to make a hydro power plant prototype using a Kaplan turbine with a laboratory scale so that it can obtain maximum output result on a micro hydro power plant. The Method of analysis used is by calculating the rimary data obtained. Prototype testing in this study uses water discharge that varies including 9 liter/s, 10 liter/s, 12 liter/s, 14 liter/s and 16 liter/s. The maximum output obtained is when the water discharge is 16 liter/s which produces a turbine rotation of 228,3 rpm before the generator is coupled and 172,5 rpm after the generator is coupled, the generator rotation is 902,5 rom, the generator voltage is 9,07 Volts, the generator current is 0,56 Amperes, generator power is 5,09 Watt, torque is 0,28 Nm, and the efficiency occurs 1,62%. Based on the result of the study, the maximum output obtained is from the water discharge 16 liter/s which is the biggest water discharge because an increase in the value of water discharge will cause the micro hydro power plant performance to increase.